A simple dual-channel imidazo[1, 5-a]pyridine-based fluorescent probe for the discrimination between Cys/Hcy and GSH. (July 2021) - Li, Yanyan; Zhang, Gongxiao; Ma, Chuanjun; Chen, Fahong; Dong, Jian; Ge, Yanqing
Abstract: A new dual-emission fluorescent probe 4-nitro-7-(4-(1-phenylimidazo [1, 5- a ]- pyridin-3-yl)phenoxy)benzo [c] (Yin et al., 2017; Jia et al., 2015; Chan et al., 2012) [1, 2, 5]oxadiazole (IP-NBD ) with high sensitivity and selectivity for the detection of cysteine (Cys)/homocysteine (Hcy) and glutathione (GSH) was designed and synthesized. The probe, which exhibits low cytotoxicity and good cell penetration ability, can quickly detect Cys/Hcy with a detection limit as low as 140/180 nM, and has been successfully tested for Cys/Hcy and GSH in cells. Graphical abstract: Image 1 Highlights: A dual-emission fluorescent probe, IP-NBD, has been developed for the detection of Cys/Hcy and GSH. The probe shows remarkable properties including high selectivity, low cytotoxicity and good biocompatibility. IP-NBD was successfully used for imaging Cys/Hcy/GSH in living cells.